A Contemporary Orthodox Approach to the Bible: Back to the Sources. (Greek Orthodox Theological Review)
The second group of evidence of a systematic application of the Orthodox hermeneutics is a large library of the Slavonic texts that came into existence with the Christian translation mission of the Orthodox Greeks to the Slavs. Greek Orthodox Theological Review 62:3-4 2017 257 A Contemporary Orthodox Approach to the Bible: Back to the Sources Ljubica Jov anovi'c This paper aims to establish the principles of the Orthodox interpretation of the Bible. However, because the majority of the twenty-first century Orthodox Churches enjoy freedom of confession and academic education, which include Biblical studies, the time is ripe to examine Orthodox Christians' approach to the Bible. Using the Seven Ecumenical Councils, which are the supreme authority in establishing Eastern Orthodox theology, it seeks the Orthodox interpretation of the Bible in the councils' teachings.